IMPLEMENTASI PEMBANGUNAN DEMOKRATISASI DI PROVINSI BANTEN (STUDI PRAKTIK POLITIK UANG PADA PILKADA SERENTAK TAHUN 2018 – 2020 DI PROVINSI BANTEN) - Agus Aan Hermawan; Yana Suharyana (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2021)
The practice of money politics is still a concern in the development of democratization in Indonesia, especially in the province of Banten. This study aims to examine the phenomenon of the mode of practice of money politics in the simultaneous regional elections of 2018 - 2020 in Banten Province. The theory used is the theory of social exchange (social exchange theory). The research method is a qualitative approach, where data collection is through observation, interviews and documentation. The results of the study found that the impetus for the practice of money politics in the 2018 - 2020 simultaneous regional elections in Banten Province, was triggered by the low economic capacity of the community, so that with rational behavior, the pros and cons, citizens as voters consider that the practice of money politics is considered a normal thing which is a natural thing in society. every election contestation, with the conditions of society that require economic sufficiency. Thus, there is little sense of rejection of the practice of money politics by citizens as voters, who are pressured by increasingly difficult and deteriorating economic conditions.